Topical imiquimod treatment of residual or recurrent cervical intraepithelial neoplasia lesions (TOPIC‐2): A randomised controlled trial - van de Sande, Anna J. M.; van Baars, Romy; Koeneman, Margot M.; Gerestein, Cornelis G.; Kruse, Arnold‐Jan; van Esch, Edith M. G.; de Vos van Steenwijk, Peggy J.; Muntinga, Caroline L. P.; Willemsen, Sten P.; van Doorn, Helena C.; van Kemenade, Folkert J.; van Beekhuizen, Helene J. (BJOG : an international journal of obstetrics and gynaecology, 2025)
To investigate the efficacy of imiquimod in women with residual or recurrent cervical intraepithelial neoplasia (rrCIN), compared with large loop excision of the transformation zone (LLETZ). Randomised controlled non-inferiority trial. One academic and one regional hospital in the Netherlands. Thirty-five women with rrCIN were included in the study between May 2016 and May 2021. Women were randomised to receive treatment with 5% imiquimod cream (12.5 mg) intravaginally (three times a week for a duration of 16 weeks) or a LLETZ procedure (standard treatment). The primary outcome was reduction to normal cytology at 6 months after starting treatment. Secondary outcomes were clearance of high-risk human papilloma virus (hr-HPV) in both groups and reduction to ≤CIN1 in the imiquimod group. Side effects were monitored. Treatment success was 33% (6/18) in the imiquimod group versus 100% (16/16) in the LLETZ group (P < 0.001), whereas HPV clearance was 22% (4/18) in the imiquimod group versus 88% (14/16) in the LLETZ group (P < 0.001). After the randomisation of 35 women, the futility of treatment with imiquimod was proven and the trial was prematurely finished. In the follow-up period, three patients remained without additional treatment, whereas all other patients underwent LLETZ, conisation or hysterectomy. In the LLETZ group none of the patients received additional treatment during 2 years of follow-up. This is the first randomised controlled trial to show that topical imiquimod has a significantly lower success rate in terms of reduction to normal cytology and hr-HPV clearance, compared with LLETZ, in women with rrCIN. Additionally, imiquimod has numerous side effects and after using imiquimod most women with rrCIN still required additional surgical treatment.